Persepsi Masyarakat Aceh Barat Terhadap Rencana Pemekaran Kota Meulaboh Sebagai Daerah Otonomi Baru - Fadhil Ilhamsyah; Zuhrizal Fadhly (Jurnal Public Policy, 2020)
This study aims to describe the factors behind the planned expansion of Meulaboh City as a New Autonomous Region and the perception of the people of West Aceh regarding the planned expansion of Meulaboh City as a New Autonomous Region. The method used in this research is quantitative research with a survey method. From the research results, it can be concluded that the majority of the people of West Aceh stated that the plan for the expansion of Meulaboh City was motivated by factors for regional economic development and regional or city development. In addition, the plan for the expansion of Meulaboh City also aims to bring services closer to the community and to get more development budgets from the Central Government. However, the plan for the expansion of Meulaboh City was not motivated by factors of injustice in the development and filling of political positions in West Aceh District. In addition, the majority of the people of West Aceh agreed to expand Meulaboh City. This attitude is influenced by various reasons including the expansion of Meulaboh City can make the city more advanced, the expansion of Meulaboh City can open new jobs, the expansion of Meulaboh City can accelerate development, and because the area of West Aceh Regency is very large.